2017
DOI: 10.1111/bjd.15125
|View full text |Cite
|
Sign up to set email alerts
|

Patients with lichen sclerosus experience moderate satisfaction with treatment and impairment of quality of life: results of a cross-sectional study

Abstract: Patients with LS are moderately satisfied with their treatment, and one-third of patients experience severe impairment of HRQoL. To improve dermatological care, we recommend enhancement of doctor-patient communication, information provision and organization, which may be more amenable to change than treatment effectiveness or safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 57 publications
2
30
0
Order By: Relevance
“…These studies found that patients reported treatment effectiveness as the most important factor for overall treatment satisfaction. 2,22,23 The group using systemic treatment presented significantly higher satisfaction scores with regard to the "effectiveness," compared with the group without systemic treatment. The "global satisfaction" was significantly higher for alitretinoin, ciclosporin, and dupilumab compared with nonsystemic treatments.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These studies found that patients reported treatment effectiveness as the most important factor for overall treatment satisfaction. 2,22,23 The group using systemic treatment presented significantly higher satisfaction scores with regard to the "effectiveness," compared with the group without systemic treatment. The "global satisfaction" was significantly higher for alitretinoin, ciclosporin, and dupilumab compared with nonsystemic treatments.…”
Section: Discussionmentioning
confidence: 94%
“…This implies that effectiveness of treatment is the major factor affecting “global satisfaction,” which is supported by previous studies on, for example, patients with psoriasis and lichen sclerosis. These studies found that patients reported treatment effectiveness as the most important factor for overall treatment satisfaction . The group using systemic treatment presented significantly higher satisfaction scores with regard to the “effectiveness,” compared with the group without systemic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, a relevant part of the patients labelled as responders are not actually clear of the disease, and this may account for a divergence between physicians' and patients' perspectives regarding treatment outcome and satisfaction. 11…”
Section: Discussionmentioning
confidence: 99%
“…Current data, probably underestimated, suggest a prevalence in the general population of 0.1–4% for cutaneous LP (2), 1.27–2.0% for oral LP (3), and 0.1–3.3% for LS (4). Few authors investigated the association between these conditions and thyroid diseases and, even fewer, the possible common etiopathogenic mechanism(s).…”
Section: Introductionmentioning
confidence: 90%